Design and Evaluation of a Solar-Powered Modular Robotic Object Maneuvering Assistance System - Rahman, S. M. Mizanoor (IEEE International Conference on Rehabilitation Robotics, 2025)
We present the design and evaluation of a solarpowered robotic object maneuvering (reaching, grasping and manipulating) system for assistance to sick, weak, and disabled people. The system is 0.78 m long and 0.4 kg heavy. The structure is made of lightweight PLA material. The front side of the system (device) acts as an end-effector, which is made of a 2-parallel jaw gripper actuated by a servomotor via a spur gear mechanism. Additional components can be attached to the inner sides of the jaws to help the gripper adjust its gripping strategies with objects of different shapes, sizes and surface textures. The back side of the device includes a rectangular groove that holds electronics circuit components such as the Arduino board, wires, batteries, etc. A solar panel is placed on the groove, which can harvest solar energy and charge the batteries to power the electronics circuit. A rotary potentiometer placed on the handle is connected to the Arduino board, which is used as a haptic input knob to control the servomotor for opening and closing the jaw-type gripper. We present the CAD model and the proof-ofconcept physical prototype of the system. We experimentally evaluate the prototype for its performance (technical specifications) and human-robot interactions using healthy subjects. The results show that the system can assist humans maneuvering objects of different shapes and surface textures and produce satisfactory human-robot interactions. The proposed system can assist sick, weak and disabled people in maneuvering objects in their daily activities, facilitate people needing upper arm rehabilitation and thus significantly improve their quality of life (QoL) even in remote areas where electricity is scarce or unavailable.